PENGARUH TINGKAT KESEHATAN DAN PENDIDIKAN TERHADAP TINGKAT PERTUMBUHAN PENDAPATAN PERKAPITA DI SUMATERA SELATAN - Syamsurijal Syamsurijal (Jurnal Ekonomi Pembangunan, 2008)
The purposes of this study are to know the direct effects of education and health on per capita income level and the indirect effect of health on per capita income level through its effect on education. A system of equations was formulated and was estimated using maximum likelihood estimation procedure. The results indicated that parameter estimates are not statistically significant at the 5 percent level of significance. However, those are theoritically sound, since the sign of coefficients in the variables is in line with existing theory. The efect of education on per capita income is positive and the indirect effect of health throuth its effect on education is also positive. The results of study suggest that the per capita income might be increased if education level of society increased through expansion of government budget on education, while health level of society should not be ignored eventhough it negates per capita income. Key Words: Health, Education, and per capita income.